1996
DOI: 10.1038/bjc.1996.255
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic treatment of human endothelial cells promotes the adherence of neutrophils in vitro

Abstract: Summary The effects of photodynamic treatment (PDT) on venules include vascular leakage accompanied by oedema formation, vasoconstriction and blood flow stasis. The goal of this study was to gain insight into the mechanism underlying these vascular events by studying one of the earliest observations after PDT, granulocyte adhesion, in an in vitro model. For this purpose human umbilical vein endothelial cells (HUVECs) preincubated with Photofrin II (PII) were illuminated with red light and incubated with neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…E-selectin. Other studies have shown that PDT-induced adherence of neutrophils to endothelial cells in vitro (de Vree et al, 1996b) and in vivo (Dellian et al, 1995;Adili et al, 1996;Sluiter et al, 1996;Rousset et al, 1999) also involved b 2 -integrins (LFA-1) (Sluiter et al, 1996;de Vree et al, 1996b). Blocking E-selectin and MIP-2 action through the use of neutralising antibodies, administered immediately after completion of PDT treatment, led to a significant reduction in neutrophil accumulation to almost baseline levels by 6 h post-treatment (PDT+anti-MIP-2 vs PDT+rat IgG: Po0.0024; PDT+anti-E-selectin vs PDT+rat IgG: Po0.04) ( Figure 5B).…”
mentioning
confidence: 99%
“…E-selectin. Other studies have shown that PDT-induced adherence of neutrophils to endothelial cells in vitro (de Vree et al, 1996b) and in vivo (Dellian et al, 1995;Adili et al, 1996;Sluiter et al, 1996;Rousset et al, 1999) also involved b 2 -integrins (LFA-1) (Sluiter et al, 1996;de Vree et al, 1996b). Blocking E-selectin and MIP-2 action through the use of neutralising antibodies, administered immediately after completion of PDT treatment, led to a significant reduction in neutrophil accumulation to almost baseline levels by 6 h post-treatment (PDT+anti-MIP-2 vs PDT+rat IgG: Po0.0024; PDT+anti-E-selectin vs PDT+rat IgG: Po0.04) ( Figure 5B).…”
mentioning
confidence: 99%
“…In one investigation, PDT of an endothelial cell monolayer led to cell retraction and exposure of an underlying fibronectin matrix, which subsequently promoted the binding of PDT-naïve neutrophils [47]. PDT of fibronectin did not increase neutrophil binding.…”
Section: 3)mentioning
confidence: 98%
“…Neutrophil adherence to the subendothelial matrix was observed in a drug dose and illumination time dependent manner. This process could be inhibited by anti- 2 -integrin antibodies, low temperature (4 °C), or staurosporin pre-incubation [134]. The central role of neutrophils in PDT was clearly proven in a rat study, where the PDT efficacy correlated with the number of neutrophils [135].…”
Section: Microvasculature Effects Related To Pdtmentioning
confidence: 99%